Urine Ratio of Neutrophil Gelatinase-associated Lipocalin to Creatinine as a Marker for Early Detection of Cisplatin-associated Nephrotoxicity (Iranian Journal of Kidney Diseases, 2015)
Introduction. Cisplatin is a widely used chemotherapeutic agent with a major side effect of nephrotoxicity. Delayed increase in serum creatinine after cisplatin injection makes serum creatinine not to be an ideal marker for early detection of cisplatin nephrotoxicity. Recently several new biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL) have been proposed for early detection of acute kidney injury (AKI). This study assessed kinetic of urine NGAL-creatinine ratio in patients who received cisplatin-containing chemotherapy. Materials and Methods. Patients with a glomerular filtration rates greater than 45 mL/min who received cisplatin-containing chemotherapy were included. Urine creatinine and NGAL concentrations were measured before cisplatin infusion and 6, 24, 48, and 72 hours after cisplatin administration. To minimize hydration effects, urine NGAL levels were adjusted according to urine creatinine. Results. Twenty-four patients were assessed. According to the Acute Kidney Injury Network criteria, 2 patients (8%) experienced cisplatin-associated AKI. The median increases in urine NGAL-creatinine ratio  were 335% (interquartile range, 320% to 350%) in the patients with AKI and 100% (interquartile range, 73% to 190%) in those without AKI (P = .02) during the first 24 hours after cisplatin administration. A urine NGAL-creatinine ratio greater than 26.9 ng/mg 24 hours after cisplatin infusion had a sensitivity of 86% and a specificity of 50% to detect cisplatin-associated nephrotoxicity. Conclusions. Urine NGAL-creatinine ratio significantly increased in patients with cisplatin-associated AKI. Urine NGAL-creatinine ratio within the first 24 hours after cisplatin infusion may better predict cisplatin-associated nephrotoxicity than serum creatinine level.